Burden of disease and benefits of exercise in fixed airway obstruction asthma - Turner, Sian Elizabeth (Curtin University, 2009)
Background and research questions. The characterization of chronic persistent asthma in an older adult population is not well defined. This is due to the difficulties in separating the diagnosis of asthma from that of chronic obstructive pulmonary disease (COPD), the latter being a condition which primarily consists of emphysema and chronic bronchitis, and in some cases asthma.The studies in this thesis focus on middle-aged and older adults with chronic irreversible asthma, or 'fixed airway obstruction asthma' (FAOA). Individuals who have FAOA are frequently labeled as having COPD and as such are rarely studied in isolation. As a consequence, little is known about FAOA and to what extent treatment strategies for COPD are relevant to individuals who present with the condition. The specific aims of the studies in this thesis were to: (i) implement and evaluate a supervised exercise training programme in middle-aged and older adults (aged 40 years and over) who had moderate to severe asthma and a degree of fixed airways obstruction; (ii) determine the similarities and differences in cardiorespiratory and dyspnoea responses with exercise testing between this population and in a cohort of subjects with COPD; and (iii) describe the burden of both asthma and COPD on hospital services in Western Australia (WA).The primary study in this thesis was a randomised controlled trial (RCT) that evaluated the effects of a 6 week supervised exercise training program in subjects with FAOA. The purpose of the study was to determine whether individuals with FAOA achieve significant improvements with a program that adhered to the guidelines for exercise training in COPD.The second study compared measures commonly collected prior to the prescription of exercise training in a cohort of individuals with COPD and a cohort of individuals with FAOA. This study arose because of unanticipated findings of low dyspnoea and a high 6 minute walk distance (6MWD) at baseline in the FAOA subjects who participated in the RCT. The FAOA and COPD cohorts were matched on the basis of pulmonary hyperinflation, or air trapping, at rest as quantified by the ratio of residual volume to total lung capacity (RV/TLC), gender and age. Comparisons were made between the groups of cardiorespiratory and dyspnoea data collected during the 6 minute walk test (6MWT), resting lung function and peripheral muscle strength.The third study utilized geographic information systems (GIS) technology to explore the distribution of respiratory health services throughout WA and hospital admissions secondary to asthma or COPD in adults aged 40 years and over during a 5 year period 2000-2004. The purpose of this study was to: (i) gain insights into issues facing the provision of respiratory services for middle-aged and older adults with asthma and COPD throughout WA; and (ii) explore the burden of asthma and COPD in middle-aged and older adults across the State.The following research questions were addressed: 1. What are the effects of a 6 week supervised exercise training program in subjects who have FAOA on quality of life (QOL), functional exercise capacity, anxiety and depression, asthma control and peripheral muscle strength? 2. What, if any, characteristics differentiate individuals who have FAOA and individuals with COPD with respect to measures of resting lung function, functional exercise capacity and peripheral muscles strength collected prior to the prescription of exercise and what is the physiological basis for any differences? 3. Does the distribution of hospital admissions for asthma and COPD in middle-aged and older adults relate to the distribution of respiratory support services for these conditions throughout WA, and are there any trends in admissions data for asthma and COPD admissions in relation to age, gender and numbers of admissions during the 5 year period of data collection?Methods. Study 1. Study 1 was a prospective RCT in which 35 subjects (16 males) were randomised using a stratified process to match for gender into an 'exercise' and a 'control group'. Subjects initially participated in a 3 week run-in period during which asthma control using the Asthma Control Questionnaire (ACQ), was assessed weekly to ensure stability of the subject's asthma. This was followed by the collection of baseline data prior to the intervention period. The run-in period was extended if a subject reported an increase in asthma symptoms as reflected by their responses to the ACQ, a variation in forced expiratory volume in one second (FEV[subscript]1) of >10% or a change in their asthma medications. Health care utilization data, comprising the number of hospitalizations and emergency department visits, exacerbations in the year preceding study entry, medications taken for asthma and co-morbid conditions were recorded.Subjects randomised to the exercise group participated in a fully supervised 6 week exercise training program consisting of three exercise classes each week at Sir Charles Gairdner Hospital. The control group received standard medical care during this 6 week period. Baseline measures were repeated immediately following the 6 week intervention period (post-intervention assessment) and at 3 months following completion of the intervention period (3 month follow-up).The measurements collected pre- and post-intervention comprised resting lung function, functional exercise capacity (6MWD), ACQ, QOL [Asthma Quality of Life Questionnaire (AQLQ) and the Medical Outcomes Study 36-item Short-Form Health Survey (SF-36)], anxiety and depression (Hospital Anxiety and Depression Scale; HAD) and peripheral muscle strength (quadriceps force and hand-grip strength). The timing of assessments was delayed if a subject experienced an exacerbation or other medical problem such that all measurements were made when subjects were in a stable condition and taking their usual medications. Health care utilization data and number of exacerbations for a 1 year period that commenced immediately after the 3 month follow-up were also collected.Study 2. Study 2 was a cross-sectional matched comparison study comparing respiratory function functional exercise capacity, cardiorespiratory and dyspnoea measures obtained during the 6MWT and peripheral muscle strength in 16 subjects (10 male) with a diagnosis of FAOA to 16 subjects (10 male) with COPD. The two groups were chosen on the basis of similar age (±5 years), gender and resting hyperinflation or air trapping (RV/TLC ±0.05). Resting lung function measurements comprised measures of airflow, lung volumes and single-breath diffusing capacity of the lung for carbon monoxide corrected for alveolar volume (DL[subscript]co/VA). All subjects completed the 6MWT during which cardiorespiratory and dyspnea responses and 6MWD were measured. The 6MWT was performed twice and data from the maximum 6MWD were used in the analyses. Quadriceps force was measured in triplicate using a strain gauge and the maximum value obtained on the subjects' dominant leg recorded. Handgrip strength was measured using a Jamar dynamometer, and the maximum force obtained from three measurements on the subject's dominant side recorded. The following data were compared in the two subject cohorts: resting lung function expressed as a percentage of predicted normal value (% predicted); maximum 6MWD; % predicted 6MWD; cardiorespiratory [oxygen saturation (Sp0[subscript]2) and heart rate] and dyspnoea responses to the 6MWT and peripheral muscle strength expressed as % predicted normal value. Data for the 32 subjects were then combined to investigate relationships between resting lung function and 6MWT data.Study 3. Study 3 was a record-linked prevalence investigation to define the prevalence, demographic characteristics and regional distribution of asthma and COPD admissions in adults aged 40 years and over in relation to the distribution of respiratory services within WA. Data on the distribution of hospitals, respiratory physicians, pulmonary rehabilitation programs and asthma educators were obtained for WA. Population data of adults aged 40 years and over were then extracted from the 2001 census released by the Australian Bureau of Statistics, and hospital admission data were obtained in a de-identified format from the Health Department of WA for the period 2000-2004 for all asthma and COPD cases. All data were aggregated according to the 30 health service areas for the State of WA which were the administrative boundaries used by the Health Department of WA at the time of data collection. Data were linked together in a geo-database using specialized GIS software and graphically displayed to show the distribution of respiratory services. Thematic maps were developed to show the proportion of adults aged 40 years and over with a primary diagnosis of asthma, a primary diagnosis of COPD, and combined data showing adults with a primary diagnosis of asthma or COPD in order to determine the proportion of admissions relative to the population size within each health service. Finally, data were aggregated in graphical format and trends in admissions data for each health service over the period 2000-2004 by gender and by age groups were identified.Results. Study 1. A total of 266 adults matched the selection criteria for the study and of these, 39 adults attended an initial screening interview. Thirty-five subjects were enrolled in the study and randomised to the exercise group or control group, of whom 34 subjects (15 male; exercise group n=19, control group n=15) completed the intervention period. The participation rate for this study was 14.7% which decreased to 12.8% with subject withdrawals. Subjects demonstrated moderate to severe airflow limitation (FEV[subscript]1 59.4±15.8% predicted) with evidence of lung hyperinflation and gas trapping (mean RV/TLC l25±19% predicted) at study entry. Subjects were aged 68±11 years. Baseline measures showed subjects to have well preserved peripheral muscle strength but significantly impaired QOL. The physical component summary score for the SF-36 was 38.l±10.0 which was significantly lower than age and gender matched Australian and WA normative data (p<0.05). The subjects had a high level of functional exercise capacity with 6MWDs close to predicted values (88±12% predicted). Dyspnoea was not a significant factor limiting performance on the 6MWT. The 6 week exercise intervention improved disease-specific QOL with the improvement being maintained at the 3 month follow-up. The magnitude of improvement in the symptoms domain and the activity limitation domain were significantly greater than any changes seen in the control group (p=0.001 and p=0.04 respectively). Six minute walk distance and anxiety levels were not significantly changed in relation to the control group though were improved in the exercise group against baseline measures.Study 2. The main findings of this study were that, despite comparable levels of pulmonary hyperinflation and air trapping, individuals with FAOA were characterized as having significantly greater 6MWD (571±88m, 95±11 % predicted versus 488±11m, 80±16% predicted p<0.005), lower scores for dyspnoea at the end of the 6MWT (2.7 ±1.8 versus 5.9±2.5, p<0.001) and preserved Sp0[subscript]2 during the 6MWT (post-exercise Sp0[subscript]2 94.7±1.9% versus 84.3±2.7%, p<0.001) than individuals with COPD. Peripheral muscle strength was similar between the two groups.Study 3. A total of 4,159 cases with a primary diagnosis of asthma and 19,970 cases with a primary diagnosis of COPD were extracted as respiratory admissions within WA during the years 2000-2004. Maps generated through GIS technology revealed a disproportionate number of hospital admissions in rural and remote areas compared to metropolitan data for adults aged 40 years and over. In addition, many parts of WA lacked the services of a respiratory physician, a hospital emergency department and access to a pulmonary rehabilitation program. Trends in admissions data showed a gradual decline in asthma admissions over the 2000-2004 time period but a rise in COPD admissions. The hospital separations for Aboriginal and Torres Strait Islander adults were high (6.7% of the COPD admissions and 16.1% of the asthma admissions) considering only 3.2% of all adults aged 40 years and over in WA are of Aboriginal and Torres Strait Islander descent. The numbers of admissions for females with asthma were consistently higher than for males within all health services whilst this pattern was reversed for the COPD admissions. With increasing age, the proportion of COPD admissions increased, and in contrast a small decline was observed in asthma admissions with increasing age.Discussion and conclusions. It is generally assumed that rehabilitation for middle-aged and older adults with chronic asthma should be similar to that prescribed for individuals with COPD subjects as the disability arising from the respiratory disease is considered to be similar. The RCT undertaken in this thesis (study 1) showed that despite the recruitment of asthmatics with fixed airflow limitation, these individuals had a higher functional exercise capacity at baseline as evidenced by 6MWDs that were close to their predicted normal values and better functional capacity than individuals with COPD recruited to studies of pulmonary rehabilitation. Participation in the exercise program for these subjects with FAOA improved QOL, however compared to a control group, the effects of the program on functional exercise capacity, asthma control, anxiety and depression, and peripheral muscle strength were not significant. A high baseline 6MWD in this cohort may however have limited the responsiveness of the 6MWT to detect a meaningful change in functional exercise capacity following training.The study comparing subjects with FAOA to those with COPD (study 2) illustrated regardless of the observations of a similar magnitude of pulmonary hyperinflation at rest in these two cohorts, the degree to which functional exercise capacity was limited differed between the two conditions and this was most likely attributable to the preservation of gas transfer in the FAOA cohort.The record linked prevalence study provided an overview of the distribution of admissions to hospitals for middle-aged and older adults with asthma and COPD and the burden placed on health services particularly in regional WA. The lack of essential respiratory services in many parts of the State and the disproportionate number of hospital admissions in rural areas compared to metropolitan areas highlighted a need for further research. The focus of this research would identify opportunities to improve the provision of health services for middle-aged and older adults with asthma and COPD in regional and remote parts of WA which may follow on to better patient outcomes for these individuals.The three studies in this thesis highlight the necessity of a correct diagnosis of an individual who has FAOA and distinguishing this from COPD as the assessment and treatment modalities for the two cohorts in terms of exercise differ. The differences in the distribution of hospital admissions data, and trends in this data with time further illustrate that a correct diagnosis of asthma versus COPD in middle-aged and older adults is important to ensure accurate evaluation of the burden of these diseases on the health care system and to plan for future services based on the need for these services in both metropolitan and regional areas.